2011
DOI: 10.2165/11586430-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Ostomy Pouch Preferences

Abstract: The results confirm that the potential attribute improvements presented to the respondents in this study significantly and positively affect the utility that patients would obtain from a potential improvement in their ostomy pouch. This provides information as to how treatment options in terms of stoma management can be structured so as to maximize the benefits for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…An SQ alternative should therefore be included to provide a real-life baseline. 19 Of 348 respondents, 282 (81%) opted for “my current treatment” in at least 1 of the choice situations, which means that some of the alternatives presented to the respondents were regarded as inferior compared with respondents’ current treatment. We noted that respondents tended to choose their current treatment more frequently when both alternatives, A and B, comprised tablets (58%) than when at least 1 of the alternatives comprised the oral film (38%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An SQ alternative should therefore be included to provide a real-life baseline. 19 Of 348 respondents, 282 (81%) opted for “my current treatment” in at least 1 of the choice situations, which means that some of the alternatives presented to the respondents were regarded as inferior compared with respondents’ current treatment. We noted that respondents tended to choose their current treatment more frequently when both alternatives, A and B, comprised tablets (58%) than when at least 1 of the alternatives comprised the oral film (38%).…”
Section: Discussionmentioning
confidence: 99%
“…This SQ alternative should be represented by attribute levels that most closely describe the respondents’ current treatment, provided that the SQ can vary for respondents. 19,20 …”
Section: Methodsmentioning
confidence: 99%
“…An SQ alternative should therefore be included to provide a real-life baseline. 19 Of 348 respondents, 282 (81%) opted for "my current treatment" in at least 1 of the choice situations, which means that some of the alternatives presented to the respondents were regarded as inferior compared with respondents' current treatment. We noted that respondents tended to choose their current treatment more frequently when both alternatives, A and B, comprised tablets (58%) than when at least 1 of the alternatives comprised the oral film (38%).…”
Section: Discussionmentioning
confidence: 99%
“…This SQ alternative should be represented by attribute levels that most closely describe the respondents' current treatment, provided that the SQ can vary for respondents. 19,20 "Protest" respondents: A "protester" is a respondent who does not make the required trade-offs when making their choices, and the expressed choices do not genuinely reflect their true preferences and values. 21 Protest respondents in our study were classified as (1) those who prefer A or B but at the same time expressed that the public sector should bear all costs, (2) those who randomly chose different options, and (3) those who for all 8 situations chose the same alternative (only A or only B).…”
Section: Dce Experimental Designmentioning
confidence: 99%
“…Furthermore, the first pouch purchase of patients in the study could be identified. Willingness-to-pay studies evaluating different pouches note that patients with ostomies tend to place value on staying on their current pouching system even if another system produces better outcomes (37). By identifying the first pouch purchase, pouch switching was analyzed when patients have least adapted to their pouching system.…”
Section: Discussionmentioning
confidence: 99%